2019
DOI: 10.3892/mmr.2019.10732
|View full text |Cite
|
Sign up to set email alerts
|

miR‑222 induces apoptosis in human intervertebral disc nucleus pulposus cells by targeting Bcl‑2

Abstract: intervertebral disc degeneration (idd) is characterized by abnormal induction of apoptosis in intervertebral disc nucleus pulposus (nP) cells. Previous studies indicated that mir-222 was upregulated in patients with rheumatoid arthritis. However, the effects of mir-222 in idd remain unclear. The present study aimed to demonstrate the role of mir-222 in nP cells. The levels of mir-222 in patients with idd were measured by reverse transcription-quantitative Pcr. cell counting Kit-8 and western blotting assays we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…IVDD is characterized by decreased cell proliferation and increased cell death. 28 In this study, downregulation of hsa_circ_0059955 significantly inhibited proliferation, and induced apoptosis of NP cells. These data indicated that decreased expression of hsa_circ_0059955 may contribute to IVDD progression.…”
Section: Discussionmentioning
confidence: 54%
“…IVDD is characterized by decreased cell proliferation and increased cell death. 28 In this study, downregulation of hsa_circ_0059955 significantly inhibited proliferation, and induced apoptosis of NP cells. These data indicated that decreased expression of hsa_circ_0059955 may contribute to IVDD progression.…”
Section: Discussionmentioning
confidence: 54%
“…There are a variety of molecular mechanisms and biological effects of ncRNAs in regulating IDD (Table S1). 83–171 NcRNAs plays a vital role in cell proliferation, cell apoptosis, cell autophagy, ECM degeneration or degradation, inflammation, and so on. Bcl‐2 is a protein related to the regulation of cell apoptosis, and the apoptosis of NPCs is an important link in IDD, so Bcl‐2 is also an important target in IDD.…”
Section: Non‐coding Rna Therapymentioning
confidence: 99%
“…Bcl‐2 is a protein related to the regulation of cell apoptosis, and the apoptosis of NPCs is an important link in IDD, so Bcl‐2 is also an important target in IDD. miRNA‐143, 83 miRNA‐155, 84 and miRNA‐222 85 have been reported to regulate the apoptosis of NPCs by targeting Bcl‐2. lncRNA‐GAS5 acts as a miRNA‐155 sponge to regulate its expression 84 .…”
Section: Non‐coding Rna Therapymentioning
confidence: 99%
“…And they delivered the up or down-regulated miR-141 through nanoparticles in the IDD rat model to aggravate or reduce experimental IDD. MiR-22215 was significantly up-regulated in degenerative NPCs. And the overexpressed miR-222 can activate Bax and caspase 3 but inhibit Bcl-2.…”
mentioning
confidence: 93%